2006
DOI: 10.1063/1.2403931
|View full text |Cite
|
Sign up to set email alerts
|

Hugoniot-compression curve of Zr-based bulk metallic glass

Abstract: Articles you may be interested inMechanical relaxation in a Zr-based bulk metallic glass: Analysis based on physical models J. Appl. Phys. 112, 033518 (2012); 10.1063/1.4745019 Shock compression response of a Zr-based bulk metallic glass up to 110 GPa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
0
18
2
Order By: Relevance
“…In the study by Turneaure et al, [12] Zr 56.7 Cu 15.3 Ni 12.5 Nb 5 Al 10 Y 0.5 was determined to have an HEL of 7.1 ± 0.3 GPa, corresponding to an elastic strain of~4 pct. Mashimo et al [23] observed a kink in the streak camera images corresponding to an HEL of 6.2 GPa in Zr 55 Al 10 Ni 5-Cu 30 BMG. Experiments performed at a peak stress exceeding the HEL yielded a two-wave structure consisting of an elastic precursor and a plastic wave, irrespective of whether the experiments were instrumented with VISAR or streak photography.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the study by Turneaure et al, [12] Zr 56.7 Cu 15.3 Ni 12.5 Nb 5 Al 10 Y 0.5 was determined to have an HEL of 7.1 ± 0.3 GPa, corresponding to an elastic strain of~4 pct. Mashimo et al [23] observed a kink in the streak camera images corresponding to an HEL of 6.2 GPa in Zr 55 Al 10 Ni 5-Cu 30 BMG. Experiments performed at a peak stress exceeding the HEL yielded a two-wave structure consisting of an elastic precursor and a plastic wave, irrespective of whether the experiments were instrumented with VISAR or streak photography.…”
Section: Introductionmentioning
confidence: 97%
“…The compression behavior of Zr 44 Nb 7 Cu 13.5 Ni 10.8 Be 24.3 has been investigated by Gong et al [22] using high-stress energy-dispersive X-ray diffraction with a synchrotron radiation source coupled with calculations of the radial distribution function at stresses up to 39 GPa. Mashimo et al [23] recently investigated the Hugoniot compression curve of Zr 55 Al 10 Ni 5 Cu 30 up to stresses of 50 GPa using the inclined mirror (IM) technique. This study by Mashimo et al [23] revealed a kink in the U s -U p data at approximately 14 GPa, which was attributed to a probable phase transition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They discovered that behind Hugoniot Elastic Limit(HEL), a concave curvature suggesting a phase-change-like transition appears on the Hugoniot curve of Vit-1 and the HEL of Vit-1 and β -Vit are about 10MPa ∼ 100MPa. T.Mashimo 6 and H.Togo 7 performed shock experiments with inclined-mirror photographic technique on Zr 55 Al 10 Ni 5 Cu 30 BMG to peak stress 45GPa, kink was observed at 14GPa in the shock velocity(Us) versus particle velocity(Up) curve, and the HEL of Zr 55 Al 10 exhibits good linearity in shock pressure from 18GPa to 110GPa, with HEL from 6.9GPa to 9.6GPa.…”
Section: Introductionmentioning
confidence: 99%
“…[22,24] There are similar mechanical hints for the initiation of plastic deformation during high pressure, high strain rate, and short duration. Turneaure et al [18] and Yuan et al [19] observed an obvious load drop in the Hugoniotcompression curves in plate impact experiments. It is speculated that the APSs could be activated simultaneously when the stress exceeds the HEL of BMGs, which causes the instantaneous stress relaxation in the Hugoniot-compression curves.…”
mentioning
confidence: 99%